Haematological indices of sickle cell patients with chronic leg ulcers on compression therapy - Oluwatoyin A. Babalola; Ayodele Ogunkeyede; Abayomi B. Odetunde; Foluke Fasola; Anthony A. Oni; Chinedum P. Babalola; Adeyinka G. Falusi (AOSIS, 2020)
Background: Recurrent chronic leg ulcers and its are morbidities associated with sickle cell anaemia (SCA). Compression therapy increases the rate of healing of these ulcers and also decreases the rate of recurrence. Objective: This study evaluated the haematological parameters of patients with SCA and chronic leg ulcers placed on high compression bandaging to provide data for improved ulcer management and prevention. Methods: Eighteen patients with SCA and chronic leg ulcers were recruited for treatment by compression therapy in Ibadan, Nigeria, from March to June 2015. Eighteen SCA patients with no history of chronic leg ulcers were age and sex matched and recruited as controls. Blood samples, wound biopsies and swabs were collected at different time points for full blood count, microbiology, culture and antimicrobial susceptibility tests. Haemoglobin variants were quantified by high performance liquid chromatography. Fasting blood sugar was tested for leg ulcer patients to determine diabetic status. Results: Ulcers ranged from 0.5 cm2 to 416 cm2 (median: 38.4 cm2). Post-intervention ulcer size ranged from 0.0 cm2 to 272 cm2 (median: 18.6 cm2, p 0.001); four ulcers completely healed. Compared to the control group, haematological indices at commencement of treatment were more severe in leg ulcer patients (p = 0.02). No patients with chronic leg ulcer was diabetic. Microorganisms isolated from the leg ulcers include Pseudomonas aeruginosa, Staphylococcus aureus, Proteus sp., Escherichia coli and Klebsiella oxytoca. Conclusion: Measures to improve haematological parameters during leg ulcer treatment in SCA patients should be taken to aid wound healing.